L- and LCL-Filtered Grid-Tied Single-Phase Inverter Transistor Open-Circuit Fault Diagnosis Based on Post-Fault Reconfiguration Algorithms - Li, Zhan; Wang, Borong; Ren, Yini; Wang, Jun; Bai, Zhihong; Ma, Hao (IEEE transactions on power electronics, 2019)
This paper presents a transistor open-circuit fault diagnosis method based on an average model and post-fault reconfiguration algorithms for a grid-tied single-phase inverter that transfers power bi-directionally. The transistor open-circuit fault occurrence is detected by comparing the average bridge arm pole-to-pole voltage deviation and threshold first. Then, the exact faulty transistor is identified by developed algorithms based on post-fault reconfiguration of control (PFRC) and of utilizing redundant leg (PFRUR). These two fault identification algorithms are suitable for different situations. Compared with the PFRUR, the PFRC can identify the faulty transistor without the help of redundant leg, but the identification time is longer. For inverters equipped with redundant leg already, the PFRUR can achieve faster identification speed so that inverters in reliability-oriented applications can return to normal operation after fault with short interruption. With average model, this method only requires existing signals sampled for control, thus it can be embedded in system easily without adding extra sensors and diagnosis circuits. The sampling frequency can be as low as switching frequency. Furthermore, this method is suitable for both inverters with L or LCL filters. Finally, experiments are carried out on a 550-W/10-kHz grid-tied single-phase inverter to verify the effectiveness.